Advances in Left Bundle Branch Pacing: Definition, Evaluation, and Applications - Zeng, Jiaxin; Xue, Siyuan; Zou, Fengwei; Qiu, Yuanhao; Zou, Jiangang (Cardiovascular innovations and applications, 2023)
Left bundle branch pacing (LBBP) emerged as a new physiological pacing strategy during the past several years. Recent observational studies have demonstrated the advantages of LBBP, including a high success rate, stable pacing parameters, and excellent clinical benefits. Widespread adoption of LBBP will depend on improvements in device/lead technology and further verification of its efficacy in large randomized clinical trials. In this review, we summarize recent advancements in LBBP, including the definition and evaluation of left bundle branch capture, LBBP applications, and future directions in this growing field.